Defect Engineering toward Highly Efficient and Stable Perovskite Solar Cells. Issue 22 (29th July 2018) - Li, Bowei; Ferguson, Victoria; Silva, S. Ravi P.; Zhang, Wei
Abstract: Metal halide perovskite solar cells are emerging candidates amongst the next‐generation thin‐film photovoltaic devices with extremely low fabrication cost and high power conversion efficiency. Defects (both in the bulk material and at the interfaces) are recognized as one of the most fundamental reasons for the compromised device performance and long‐term stability of perovskite solar cells. In this review article, the authors analyze the possible origins of the defects formation in metal halide perovskites, followed by the rationalization of various approaches being utilized to reduce the density of defects. The authors demonstrate that defect engineering, including adding dopants in the precursor solutions, interface passivation, or other physical treatments (thermal or light stress), is an essential way to further boost the device performance and enhance their long‐term stability. The authors note that although the exact mechanisms of defect elimination in some approaches are yet to be elucidated, the research on defect engineering is expected to have enormous impact on next wave of device performance optimization of metal halide perovskite solar cells toward Shockley–Queisser limit. Abstract : In this review article, the authors analyze the possible origins of the defects (both in the bulk material and at the interfaces) in perovskite solar cells and summarize various approaches being utilized to reduce them. The authors demonstrate that defect engineering is an essential way to further boost the device performance and enhance their long‐term stability.